Human rights violation of trans women in Umlazi Township, South Africa: an interpretive phenomenological analysis study - Ruth Ntombifuthi Luthuli; Idah Moyo; Azwihangwisi Helen Mavhandu-Mudzusi (Health Psychology and Behavioral Medicine)
This paper reports on human rights violation of trans women in Umlazi township in South Africa. Violation of trans women’s human rights happens in several countries regardless of their constitutional stance regarding LGBTQI policies. Although South Africa was the first country to outlaw discrimination based on sexual orientation with its democratic Constitution of 1996, it is not an exception to these violations of transgender people’s human rights. This paper presents human rights violations experienced by trans women’s in Umlazi township in South African. The study was qualitative in nature utilising an interpretative phenomenological analysis design. Data was collected through semi-structured interviews from eight criterion purposively selected trans women from Umlazi township. Data was analysed guided by an interpretative analytics framework. Two key themes emerged from the study: the types of human rights violations and their sources. The findings indicated that trans women experience several types of human rights violations, including violations of their right to safety, freedom of expression, access to employment, and the right to human dignity. The sources of these human rights violations for trans women include cis-normative infrastructure, transphobic communities, and transphobic public officials. Understanding these experiences is crucial in developing measures to conscientize communities, foster tolerance and promoting social inclusivity of transgender people in society. The findings provide insights that can facilitate positive changes in how communities perceive transgender persons.